2014
DOI: 10.1111/jgs.12786
|View full text |Cite
|
Sign up to set email alerts
|

Licensed Nurse Staffing and Health Service Availability in Residential Care and Assisted Living

Abstract: Structured Abstract Objectives To create data driven typologies of licensed nurse staffing and health services in residential care/assisted living (RC/AL). Design Cluster analysis was used to describe the patterns of licensed nurse staffing and 47 services, and the extent to which these clusters were related. Setting RC/AL communities in the United States. Participants A convenience sample of administrators and health care supervisors from 89 RC/AL communities in 22 states. Measurement RC/AL character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 20 publications
0
46
0
Order By: Relevance
“…All 3 may be linked to lower levels of clinical oversight and services. 70 DAL facilities from rural regions were also those with lower levels of professional staffing and service availability. Others have shown that a higher proportion of licensed nursing staff hours (whether RN or LPN) or more hours of RN staff time per resident might reduce hospitalization risk in residential care and AL.…”
Section: Discussionmentioning
confidence: 98%
“…All 3 may be linked to lower levels of clinical oversight and services. 70 DAL facilities from rural regions were also those with lower levels of professional staffing and service availability. Others have shown that a higher proportion of licensed nursing staff hours (whether RN or LPN) or more hours of RN staff time per resident might reduce hospitalization risk in residential care and AL.…”
Section: Discussionmentioning
confidence: 98%
“…Given the limited staff and nurse availability in many ALs (Beeber et al, 2014), the difficulty of managing daily life and care for an aging resident population, and the housing of persons with serious, ongoing mental illness may present challenges. While U.S. health privacy policy forbids discussing others’ diagnoses or health conditions with residents, mental illnesses create challenging experiences that can diminish the quality of life of other residents.…”
Section: Discussionmentioning
confidence: 99%
“…Assisted living [AL] communities were developed to care for older adults with limited need for support and oversight in a less medically-focused environment than a nursing home (Becker, Schoenfeld & Stiles, 2002; Chapin & Dobbs-Kepper, 2001; Wilson, 1990); not all ALs have a full-time, licensed nurse on staff (Beeber et al, 2014; Hawes 2003). However, intentionally or not, many ALs also house persons with SMI (McGrew, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Already, assisted living has demonstrated its ability to care for residents with dementia who do not have ongoing medical needs [14,15], and many assisted living residences provide nursing services [16]. Although assisted living residents can contract for rehabilitation services when necessary, nursing homes will likely remain the main provider of residential acute and rehabilitative care, and assisted living In contrast to the dining environment of a traditional nursing home, the kitchen and eating area in a Green House home are designed to resemble those of a private home.…”
Section: New Models Of Residential Long-term Carementioning
confidence: 99%